Designing and analyzing park sensor system for efficient and sustainable car park area management - Karakebelioglu, Ahmet Faruk; Eren, Ozkan; Koten, Hasan; Alp, Huseyin (Sustainable Engineering and Innovation, 2021)
Many problems have been seen in cities because of increasing vehicle density. One of these problems is vehicle density in parking lots. People look for empty parking areas and they spend too much time. While people look for empty parking areas, CO2 (carbon dioxide) emission and energy consumption increase due to density in parking lots. We worked to solve these problems by doing Magnetic Car Park Sensor. Magnetic Car Park Sensor is the system which detects cars in car parks. After cars detected with the system, the system sends information to center server and we can see information data in the system interface. The system helps people to find empty parking lots. As people find empty car park areas fastly, energy consumption and CO2 emission are decreased significantly.